Recycling of waste expanded polystyrene as an effective adsorbent of naphthalene from aqueous solution - Taiwo, Oluwayemisi Christiana (Array, 2021)
Batch adsorption process factors [contact time (20–150 min), adsorbent dosage (0.5–1.5 g), adsorbate concentration (5–30 mg l–1), and agitation rate (100–250 rpm)] were optimised based on D-optimal Design under the Response Surface Methodology (RSM) of the Design-Expert Software (7.6.8) for the removal of naphthalene from aqueous solution using adsorbent developed from Acetylated Waste Expanded Polystyrene (AWEPs). The maximum adsorption capacity (5.6608 mg g–1) achieved was well fitted to Dubinin-Radushkevich Isotherm (R2 = 0.9949). The SSE (< 0.05) and ARE (< 4.0 %) indicated pseudo- second-order as the most suitable model. This research has demonstrated the effectiveness of the WEPs for the removal of naphthalene from the aqueous solution.